Finish your plate! Food disposition behaviour among late adolescents. Issue 9 (17th August 2021) - Lim, Tze-Yin; Lim, Bibiana; Leong, Choi-Meng; Le, Andrea
Abstract : Purpose: This study explores the disposition behaviour of late adolescents towards unfinished food. Specifically, this paper identifies and discusses the manner (the how's) and the reasons (the why's) of food disposition. Design/methodology/approach: This study adopted a taxonomy of decisions pertaining to consumer disposition processes. A generic qualitative approach based on personal interviews and focus group discussions was used to collect data from late adolescents. Data was subsequently analysed using content and thematic analyses. Findings: The findings revealed five manners (the how's) of food disposition among late adolescents, namely keeping it for original purposes, leaving it for other people to dispose of, converting it for another purpose, trying to finish it and getting rid of it permanently. Additionally, there are three reasons (the why's) for food disposition among late adolescents, namely food-related factors, socio-cultural factors and personal factors. Originality/value: Food waste has continually impacted food production, supply and consumption in a profound way. Responsible food disposition behaviour among individuals has become essential to improve food sustainability. Proper food disposition requires a behavioural change among individuals, including late adolescents, who are growing into adulthood. This study contributes to the body of knowledge of food systems by identifying how and why food is disposed of among late adolescents during their formative years. The findings can be utilised to raise awareness of food disposition behaviour and design food responsibility initiatives.